Dysplasia epiphysealis hemimelica (Trevor’s disease): a rare case report with oral manifestations - ML, Asha; BN, Nagaraj; G, Arun Kumar; ML, Ashok (International Journal of Research in Medical Sciences, 2017)
Dysplasia epiphysealis hemimelica, also known as Trevor’s disease, is an extremely rare skeletal developmental disorder of unknown etiology, characterized by an osteocartilaginous outgrowth of one or more epiphyses or of a tarsal bone during childhood. It is a rare skeletal hemimelica disorder characterized by asymmetric growth of cartilage in one or more epiphyses. Due to the unusual presentation and variability of the picture, there is no standardized treatment and outcome is very different. Also such an unusual, unique case with craniofacial manifestations has not been reported in the literature. We report a case of a 14-year-old male, who complained of irregularly placed teeth in upper and lower front teeth region. On general physical examination we noticed some skeletal abnormalities with the patient and hence we subjected him to radiographic investigations. The images were consistent with epiphyseal dysplasia hemimelica. The prognosis of DEH is variable and depends basically on its location and size. Carriers of this unusual dysplasia should be periodically monitored for the risk of recurrence.